Micromechanical modeling of triphasic granular media - Amiya Prakash Das; Jidong Zhao; Thomas Sweijen (Proceedings of the National Academy of Sciences, 2025)
This paper presents pore unit assembly-discrete element model (PUA-DEM), a pore-scale hydromechanical framework that resolves interactions between mobile granular particles and multiphase fluids in unsaturated granular media. The framework uniquely integrates DEM with pore-scale hydrodynamic models to capture unsaturated flow dynamics, while leveraging a two-way coupling mechanism to ensure bidirectional fluid–grain feedback through stabilized domain partitioning. Further innovations include a dynamic pore-merging and retriangulation algorithm that enhances computational efficiency for large-scale systems. Validated against experimental data for glass beads and Ottawa sand, PUA-DEM accurately reproduces critical hydromechanical phenomena-including capillary/viscous fingering, wetting-induced granular swelling/collapse, and quasi-static deformation-under diverse saturation and loading regimes. Numerical case studies reveal how capillary forces and wetting fluid saturation collectively govern granular response, from pore-scale meniscus evolution to macroscale flow instabilities. By bridging pore- and particle-scale physics, PUA-DEM advances predictive modeling of partially saturated granular systems, offering transformative insights for geohazard mitigation, sustainable agriculture, pharmaceutical manufacturing, and energy-related engineering applications.